Kebebasan Beragama di Indonesia perspektif Ratio Legis Hukum Riddah - Nur Rofikoh (Prodi Hukum Pidana Islam Fakultas Syari’ah dan Hukum Universitas Islam Negeri Sunan Ampel Surabaya, 2017)
Abstract: This article discusses about the freedom of religion in Indonesia according to riddah law ratio legis. In Indonesia, the guarantee of religious freedom is in the 29th article of 2nd paragraph in the 1945 Constitution that someone is free to choose and embrace a particular religion. Persons who convert from one religion to another shall not be punished, except those whose religion denounces, abuses or condemns oother religions which may be punished. The act is regulated in the article 156a of the Criminal Code concerning the prohibition of abuse or defamation of religion. Islam guarantees freedom of religion as the Qur'anic verse of al-Baqarah verse 256 that there is no compulsion to enter Islam. In a Islamic law, a person who comes out of Islam is called apostate and his blood is halal to be killed. The act is included in the category of riddah jarîmah which can be sentenced a hadd punishment, death penalty. Nevertheless, there are some opinions that in Islamic law not all people come out of Islam can be put to death, only those who emerge from their religion that cause rebellion, chaos on the earth that can be killed. Keywords: Religious freedom, Indonesia, ratio legis, riddah. Abstrak: Artikel ini membahas tentang kebebasan beragama di Indonesia menurut ratio legis hukum riddah. Di Indonesia, jaminan atas kebebasan beragama terdapat dalam pasal 29 ayat 2 UUD 1945. Warga yang melakukan pindah agama satu ke agama yang lain tidaklah dikenai hukuman, kecuali mereka yang dalam agamanya mencela, menghina atau menista agama lain yang dapat dijatuhi hukuman. Perbuatan tersebut diatur dalam pasal 156a KUHP tentang larangan melakukan penyalahgunaan atau penodaan terhadap agama. Islam menjamin kebebasan beragama sebagaimana nash al-Qur’an surah al-Baqarah ayat 256, bahwasanya tidak ada paksaan untuk memasuki agama Islam. Dalam hukum Islam, seseorang yang keluar dari agama Islam disebut murtad dan halal darahnya untuk dibunuh. Perbuatan tersebut masuk dalam kategori jarîmah riddah yang dapat dijatuhi hukuman hadd yakni hukuman mati. Meski demikian, ada beberapa pendapat bahwa dalam hukum Islam tidak semua orang keluar dari Islam dapat dihukum mati, hanya orang yang keluar dari agamanya yang menimbulkan pemberontakan, kekacauan di muka bumilah yang dapat dihukum mati. Kata Kunci: Kebebasan beragama, Indonesia, ratio legis, riddah.